2007
DOI: 10.1111/j.1349-7006.2007.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of hepsin and hepatocyte growth factor activator inhibitor type 2 expression in renal cell carcinoma

Abstract: Cell surface proteolysis is important for the generation of bioactive proteins mediating tumor progression. Recent studies suggest that the membrane-anchored cell surface proteinases matriptase and hepsin have significant roles in tumors. We analyzed the expression and clinical relevance of matriptase and hepsin, and their inhibitors hepatocyte growth factor activator inhibitor type 1 (HAI-1) and type 2 (HAI-2) in 66 cases of conventional renal cell carcinomas (RCC). The mRNA level was evaluated in paired samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 43 publications
(84 reference statements)
2
59
0
3
Order By: Relevance
“…Studies with preclinical prostate cancer models suggested that hepsin may play a role in invasive cancer growth and cancer progression (28,29). Moreover, gene expression analyses have also implicated hepsin in ovarian cancer (30), renal cell carcinoma (31,32), and endometrial cancer (33). A putative function of hepsin in tumor progression could be related to its enzymatic activity toward the macromolecular substrates pro-HGF (19,34), pro-uPA (35), and laminin-332 (36).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with preclinical prostate cancer models suggested that hepsin may play a role in invasive cancer growth and cancer progression (28,29). Moreover, gene expression analyses have also implicated hepsin in ovarian cancer (30), renal cell carcinoma (31,32), and endometrial cancer (33). A putative function of hepsin in tumor progression could be related to its enzymatic activity toward the macromolecular substrates pro-HGF (19,34), pro-uPA (35), and laminin-332 (36).…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of the HGF/c-Met signaling axis can lead to aberrant cell proliferation and drug resistance and promote cell migration, invasive growth, and angiogenesis (3)(4)(5)(6)(7)(8)(9), and is observed in many malignancies, including those of the pancreas, lung, stomach, breast, and kidney (3,5,(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…20 Moreover, significant roles of matriptase and hepsin in progression of cancers in other organs are also reported. [21][22][23] Previously we reported that the targeted disruption of Hai-1/Spint1 in mice resulted in embryonic lethality and impaired placental development with a defect of the labyrinthin layer. 10 The placental defect in Hai-1/Spint1…”
mentioning
confidence: 99%